2013
DOI: 10.1371/journal.pone.0067195
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Methylated XAF1 DNA Indicates Poor Prognosis for Gastric Cancer

Abstract: BackgroundMethylated DNA in fluids may be a suitable biomarker for cancer patients. XAF1 has been shown to be frequently down-regulated in human gastric cancer (GC). Here, we investigated if XAF1 methylation in GC could be a useful biomarker.MethodsReal-time RT-PCR was used to detect XAF1 mRNA expression; immunohistochemistry and western blot were used to examine XAF1 protein expression in GC tissues (n = 202) and their corresponding para-cancerous histological normal tissues (PCHNTs). Real-time methylation sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…The present study demonstrated an association between incidence of VM and reduced expression of XAF1; the incidence of VM was significantly increased in XAF1-underexpressing samples. This provides a novel fundamental mechanism for an effect reported previously that decreased XAF1 expression is associated with poor prognosis in numerous types of cancers (30,31).…”
Section: Discussionmentioning
confidence: 74%
“…The present study demonstrated an association between incidence of VM and reduced expression of XAF1; the incidence of VM was significantly increased in XAF1-underexpressing samples. This provides a novel fundamental mechanism for an effect reported previously that decreased XAF1 expression is associated with poor prognosis in numerous types of cancers (30,31).…”
Section: Discussionmentioning
confidence: 74%
“…For example, epigenetic patterns altered within the promoter region of XAF1 genes have been identified in tumors. Hypermethylation of CpGs sites located in the 5' proximal region was found to be associated with transcriptional silencing of XAF1 in gastric cancer (14,23), urogenital (24) and colon (25) cancer cell lines. However, epigenetic modifications are extremely complex and other XAF1 associations have been observed.…”
Section: Xaf1 Expression Levels In a Non-small Cell Lung Cancer Cohormentioning
confidence: 97%
“…The peroxidase activity was developed by incubating with 0.1% 3,3-diaminobenzidine (Sigma) in PBS with 0.05% H2O2 for 5 min at room temperature. As described methods in our previous studies [42,43], based on the frequency and intensity of staining, the scores of histochemical staining were determined by three independent clinical pathologists, and the inconsistent results were finally determined after discussion.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…The western blotting analysis was carried out using Immobilon-P polyvinylidene difluoride membranes (Millipore, 28820 Single Oak Drive, Temecula, California 92590, USA) as described in previous studies [42,43]. The cell lysates were separated on sodium dodecyl sulfate-polyacrylamide gels and the western blotting analysis was carried out with following antibodies against CSMD1, Cyclin D1 (Santa Cruz Biotechnology), Snail (Abgent Inc, CA, USA), E-cadherin, Vimentin, Twist, Zeb1 (Cell Signaling Technology, MA, USA), iNOS, NFκB-p65, NFκB-p50 (Abcam, Cambridge, CB4 0FL, UK), and c-MYC (Sigma Chemical Co., MO, USA), respectively.…”
Section: Western Blotting Analysismentioning
confidence: 99%